2017
DOI: 10.7566/jpsj.86.114003
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Wave State in the Nonlinear Kramers Equation for Self-Propelled Particles

Abstract: We study collective phenomena of self-propagating particles using the nonlinear Kramers equation. A solitary wave state appears from an instability of the spatially uniform ordered state with nonzero average velocity. Two solitary waves with different heights merge into a larger solitary wave. An approximate solution of the solitary wave is constructed using a self-consistent method. The phase transition to the solitary wave state is either first-order or second-order, depending on the control parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…However, the amplitude difference increases at successive collisions and only one solitary wave survives after a long time. This behavior is slightly different from the head-on collision of two solitary waves in our previous model [11], where merging occurred at the first collision. The reason for the difference is not clear; however, it is not so surprising because various phenomena such as pair annihilation, interpenetration, and the formation of a bound state occur at the head-on collision of two general dissipative solitons depending on the control parameters [15,16].…”
Section: One-dimensional Systemcontrasting
confidence: 85%
See 3 more Smart Citations
“…However, the amplitude difference increases at successive collisions and only one solitary wave survives after a long time. This behavior is slightly different from the head-on collision of two solitary waves in our previous model [11], where merging occurred at the first collision. The reason for the difference is not clear; however, it is not so surprising because various phenomena such as pair annihilation, interpenetration, and the formation of a bound state occur at the head-on collision of two general dissipative solitons depending on the control parameters [15,16].…”
Section: One-dimensional Systemcontrasting
confidence: 85%
“…2(d). In the previous paper, we constructed a similar phase diagram for the nonlinear Kramers equation with velocity as the variable [11]. Figure 3 shows a head-on collision of two solitary waves with slightly different amplitudes at g = 2, L x = 10, α = 5, and T = 0.1.…”
Section: One-dimensional Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several discussions about the formation mechanism of the solitary wave state, however, it is not clearly understood yet [16]. In previous papers, we showed that the solitary wave state can appear in the nonlinear Kramers equation [17] for the probability distribution of the position and velocity of self-propelled particles. Furthermore, we proposed a simple model of one-dimensional solitary wave state, in which the linear instability of the uniform disordered state leads to the formation of a solitary wave state [18].…”
Section: Introductionmentioning
confidence: 93%